AMERICA INVENTS—AND SO CAN YOU? THE DICHOTOMY OF SUBJECT-MATTER ELIGIBILITY CHALLENGES IN POST-GRANT PROCEEDINGS - Ho, Krystina L. (Columbia law review, 2015)
In 2011, Congress passed the Leahy-Smith America Invents Act, a broad-sweeping reform of the American patent system. Within this landmark piece of legislation, Congress created trial-like administrative proceedings as a cost-effective alternative to litigation. Inter partes review allows third parties to go before the Patent and Trademark Office and attempt to invalidate an already issued patent on the limited grounds that it fails to meet either novelty or nonobvious standards. For a brief, nine-month period following patent issuance, however, a different administrative proceeding governs: post-grant review. With PGR, third parties can bring invalidity challenges that are unavailable to them at IPR—such as the claim that the invention does not encompass patentable subject matter. This Note aims to understand the effect of limiting administrative subject-matter eligibility challenges to a discrete nine-month window, labeling this phenomenon the "IPR—PGR dichotomy" in the process. It argues that, much like common statutes of limitations, the nine-month barrier incentivizes third parties to bring their subject-matter eligibility claims early. But as a consequence, smaller companies and individual inventors will likely be shut out, with only big businesses able to make use of the advantages PGR presents. As such, the Note advocates for legislative reform that would allow more third parties, including the "little guy," to bring subject-matter eligibility challenges before the PTO.